Upstream Open Reading Frames and Human Genetic Disease - Barbosa, Cristina (2015)
Abstract: In many eukaryotic messenger ribonucleic acids (mRNAs) one or more short upstream open reading frames (uORFs) precede the initiation codon of the main coding region. For example, in human cells, uORFs are present in about half of the transcripts. Emerging ribosome profiling and peptidomics analyses have recently shown that these uORFs are translated into polypeptides that seem to serve important biological functions. In addition, very interesting examples have shown that these uORFs are cis-acting RNA elements that can impact gene expression by repressing translation of the downstream main ORF under control conditions and derepressing it under certain pathophysiological stresses. Furthermore, evidence from genetic and bioinformatic studies implicate disturbed uORF-mediated translational control in the aetiology of human diseases. Identifying more cases and understanding the aberrant mechanisms of uORF-mediated translational control, as well as discovering the biological function of the uORF-encoded polypeptides, is fundamental to advance in diagnosis, prognosis and treatment of many human disorders. Key Concepts: Upstream open reading frames (uORFs) are cis-acting RNA elements involved in translational regulation, which precede the initiation codon of the main coding region. For a uORF to function as a translational regulatory element, its initiation codon must be recognised, at least at certain times, by the scanning 40S ribosomal subunit and associated translation initiation factors. uORFs can impact gene expression by repressing translation of the downstream main ORF under control conditions, and derepressing it under certain pathophysiological stresses. The impact the uORFs can have on translation depends on variables, such as (1) the distance between the 5′ cap and the uORF, (2) the context in which the uORF AUG (or non-AUG) is located, (3) the length of the uORF, (4) the sequence and secondary structure of the uORF, (5) the number of uORFs per transcript, (6) the position of the uORF termination codon and (7) the length of the intercistronic sequence(s). uORF-encoded polypeptides might serve functional roles in cells. Polymorphisms or mutations that introduce/eliminate uORFs or modify the uORF-encoded peptide can cause human disease. Understanding the mechanisms through which the uORFs regulate gene expression may lead to innovation in diagnosis, prognosis and treatment of many human disorders.